PERAN TUTOR SEBAGAI FASILITATOR DALAM MENINGKATKAN KEMANDIRIAN BELAJAR PESERTA DIDIK PAKET C DI SKB KOTA SERANG - Sudrajat, Indra; Pertiwi, Fitri (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2020)
This research was conducted with the objectives of knowing the role of tutors as facilitators in increasing the learning independence of Package C students. at SKB Serang City. This research was conducted using descriptive qualitative research methods. And the research subject who was used as a resource in this study was a Package C tutor who also handled the Dapodik section. From the results of this study it can be known that the level of independence of the learning community is still in the average category and still needs to be improve, because this learning independence can help students increase self-confidence, improve the ability to understand information, to improve the attitudes and behavior of students. Based on this, learning independence needs to be applied by students because later it will help students in dealing with life in society.